PERLINDUNGAN KONSUMEN TERHADAP TERJADINYA KENAIKAN TAGIHAN LISTRIK (Studi Kasus Masa Pandemi COVID-19) - Retanti Purwanti, (2022)
In modern life, electricity is a very important element for people's lives, because electricity acts as the main resource needed to support people's daily activities. PT. PLN as a party that provides electricity as well as an electricity business actor, in providing electricity imposes a bill that must be paid by consumers who use electricity. The rise of cases of rising electricity bills where electricity bills rise unnaturally occurred during the COVID-19 pandemic, so consumer protection is very much needed in this problem. The purpose of this study is to find out how legal protection is for consumers against the increase in electricity bills during the COVID-19 pandemic, as well as what legal remedies can be taken by consumers who experience losses due to the increase in electricity bills carried out by PT. PLN. The research method used in this research is normative juridical research and the approach used is the statutory approach. The results of this study conclude that consumer protection for electricity service users is preventive and repressive, and follows the rules of the Consumer Protection Act and the Electricity Act. Consumers are entitled to compensation or compensation for the losses they experience, PT. PLN as a business actor provides compensation to consumers in the form of installment payments for the increase in electricity bills during the COVID-19 pandemic. In addition, consumers can take legal action, namely litigation or non-litigation. Litigation efforts through the court in a civil manner, which can be submitted individually or in groups (class action). Meanwhile, non-litigation through the Consumer Dispute Settlement Agency or alternative dispute resolution. In addition to the two efforts above, consumers and business actors can also resolve disputes peacefully.